Factors delaying chemotherapy for breast cancer in four urban and rural oncology units. Issue 7 (18th September 2012) - Fox, Peter N.; Chatfield, Mark D.; Beith, Jane M.; Allison, Stuart; Della‐Fiorentina, Stephen; Fisher, Dean; Turley, Kim; Grimison, Peter S.
Abstract Background Delays in commencing adjuvant chemotherapy for early breast cancer beyond 12 weeks are associated with increased mortality. The aim of this study was to identify factors delaying chemotherapy in an inner metropolitan, outer metropolitan, small rural and large rural cancer centre in New South Wales, Australia. Methods We retrospectively reviewed 400 consecutive patients that received adjuvant chemotherapy for stages I–III breast cancer. We evaluated factors affecting time from primary and definitive surgery until commencing chemotherapy. Results The primary factor associated with chemotherapy delays was the geographic location of the cancer centre. The median time from primary surgery to chemotherapy was longer for the large rural centre (median 58 days), compared with the outer metropolitan (45 days), small rural (39 days) and inner metropolitan centre (33 days). Treatment delays in the large rural centre were associated with higher rates of multiple operations (43% versus 31% elsewhere), mainly because of more staged axillary dissections (34% versus 19%), and longer time from definitive surgery to oncology assessment. Conclusion Patients in the large rural centre, who are served by fly‐in medical oncology services, are more likely to experience delays in receiving adjuvant chemotherapy for early breast cancer. Strategies to reduce delays include use of intraoperative frozen section analysis, multidisciplinary meetings, improving efficiency in pathology reporting and employment of a breast cancer care coordinator and an on‐site medical oncologist.